EXPERIMENTAL STUDY OF PARAFFIN-BASED PCM THERMAL STABILITY AFTER REPEATED THERMAL CYCLES FOR ENERGY STORAGE APPLICATIONS - Dondi Kurniawan; Muhammad Irsyad; Apri Wiyono; Ahmad Yonanda; Angga Darma Prabowo; Ardika Kusuma (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Paraffin-based phase change materials (PCMs) have great potential in thermal energy storage due to their ability to absorb and release energy during the freezing and melting processes. However, the stability of their thermal characteristics after undergoing repeated heating and cooling cycles remains a challenge for long-term applications. This study aims to evaluate the phase change temperature characteristics and latent heat capacity of paraffin after undergoing 0, 200, 400, and 600 repeated thermal cycles using Differential Scanning Calorimetry (DSC) and T-history tests. The test results show that despite a slight decrease in freezing, melting temperatures changes in chemical structure after a number of cycles, paraffin still maintains its capacity to absorb and release energy quite efficiently. The latent heat capacity decreased from 142.77 J/g to 126.02 J/g over 600 cycles during the melting process. However, during the freezing process, it increased from 139.25 J/g to 147.55 J/g. These findings provide a scientific basis for optimizing paraffin-based PCM for reliable and sustainable thermal energy storage applications.